Impact of digital health management on clinical outcomes during post-PCI outpatient care in patients with acute coronary syndrome: study protocol for a multicentre, randomized controlled trial - Yu, Hang; Zhang, Wei; Li, Guoliang; Chen, Tao; Dang, Shaonong; Ma, Xiaofeng; Zhang, XiaoWei; Ma, Xiaofeng; Hong, Zhibin; He, Pengyi; Xu, Xiaohui; Chen, Xiuying; et al. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionCoronary heart disease is becoming more common in developing nations. Acute coronary syndrome (ACS) poses a major challenge to global health; however, access to cardiac rehabilitation and preventative measures is limited. There is an urgent need for affordable and widely accessible alternative delivery models to resolve this treatment gap. Research conducted by both local and international experts has focused on the role of smartphones in offering rehabilitation guidance and secondary prevention for patients. Rehabilitative effects have mainly been observed in areas where risk factors and behavioural adjustments can be altered. However, high-quality, evidence-based randomized controlled trials (RCTs) are lacking. Furthermore, the previous studies were single-centre studies with restricted case sources, thereby leading to relatively weak external validity of the research findings. Additionally, most of the previous studies have evaluated cardiac function indicators, with limited assessments of patients' clinical endpoint indicators, quality of life, and psychological aspects.Method and analysisThe purpose of this study is to explore the development of a smartphone-based systematic and extensible digital management model for post-percutaneous coronary intervention (PCI) outpatient care among ACS patients. We aim to assess whether the integration of a digital management model with conventional postoperative follow-up management is more beneficial for patient recovery during the outpatient rehabilitation process than conventional postoperative follow-up management alone. We propose a single-blind, multicentre RCT of 1,366 ACS patients who underwent PCI and who completed 12 months of follow-up. In the experimental group, within one year after discharge, participants will receive both the current standard postoperative follow-up management and additional management via a digital platform. In the control group, within one year after discharge, participants will receive only the current standard postoperative follow-up management. The primary clinical endpoint of this study is major adverse cardiovascular and cerebrovascular events (MACCEs), whereas the secondary clinical endpoints include cardiac function indicators, quality of life scores, and mental health scores, among other endpoints.ConclusionsThis clinical trial will provide evidence to demonstrate whether digital health management is a better approach for improving clinical outcomes in patients with post-PCI ACS.If proven effective, this digital model could address the global underutilization of cardiac rehabilitation by providing scalable, low-cost solutions, particularly in rural and resource-limited settings. Clinically, it may reduce MACCEs and improve quality of life, while public health systems could integrate this approach to alleviate workforce shortages and geographic barriers.Trial Registration Numberhttps://www.clinicaltrial.gov, identifier ChiCTR2400086452.